The specific IgM response to Mycoplasma pneumoniae infection: interpretation and application to early diagnosis. - Moule, J. H. (Cambridge University Press, 1987)
Specific IgM antibody production in patients with serologically proven Mycoplasma pneumoniae infection by the complement fixation (CF) test was studied using a mu-capture ELISA. Sera from 79% of patients were found to be IgM positive. Patients could be divided into two groups relating to the amount of specific antibody produced. High levels of specific IgM (greater than or equal to 10 units) were more commonly found in younger patients. Seventy-six per cent of patients under the age of 20 produced relatively high levels of IgM compared to 35% of patients over the age of 20. In contrast, the number of patients who produced low or undetectable levels of IgM (less than 10 units) was found to increase with age. This trend was found to be significant which suggests that low or undetectable levels of IgM may be due to reinfection with M. pneumoniae. Specific IgM was found to appear in the serum at approximately 7 days after the onset of symptoms, peaking at between 10 and 30 days, and then falling to undetectable levels at an estimated 12-26 weeks post onset of symptoms. Twenty-eight per cent of acute-phase sera (CF titres less than 256) from patients whose sera subsequently showed a fourfold or greater rise in M. pneumoniae CF antibody titre were IgM positive. Thus using mu-capture ELISA a diagnosis of M. pneumoniae infection may often be made more rapidly than by the complement fixation test.